2005
DOI: 10.1126/science.1118957
|View full text |Cite
|
Sign up to set email alerts
|

Super-Compressible Foamlike Carbon Nanotube Films

Abstract: We report that freestanding films of vertically aligned carbon nanotubes exhibit super-compressible foamlike behavior. Under compression, the nanotubes collectively form zigzag buckles that can fully unfold to their original length upon load release. Compared with conventional low-density flexible foams, the nanotube films show much higher compressive strength, recovery rate, and sag factor, and the open-cell nature of the nanotube arrays gives excellent breathability. The nanotube films present a class of ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
475
4
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(521 citation statements)
references
References 21 publications
37
475
4
5
Order By: Relevance
“…To be able to solder the bottom of the CNT cooler blocks on the back side of the chips, both surfaces were cleaned and sputtered up with a thin ϳ50 nm layer of chromium ͑adhesion promoter͒ and subsequently with a solderable copper film of ϳ2 m average thickness. Owing to the individual and collective mechanical strengths 15 during the assembly and testing phases of the experiments, no any damage or degradation of the nanotube films was observed proving the robustness and feasibility of CNT cooler structures for practical applications. The assembly was measured on a probe station to record the chip temperature versus heating power characteristics under various thermal loads ͑up to ϳ7 W͒ and cooling gas flow rates ͑N 2 at 0-2 l min −1 ͒ with a flow perpendicular to the upper facet of the chip.…”
mentioning
confidence: 94%
“…To be able to solder the bottom of the CNT cooler blocks on the back side of the chips, both surfaces were cleaned and sputtered up with a thin ϳ50 nm layer of chromium ͑adhesion promoter͒ and subsequently with a solderable copper film of ϳ2 m average thickness. Owing to the individual and collective mechanical strengths 15 during the assembly and testing phases of the experiments, no any damage or degradation of the nanotube films was observed proving the robustness and feasibility of CNT cooler structures for practical applications. The assembly was measured on a probe station to record the chip temperature versus heating power characteristics under various thermal loads ͑up to ϳ7 W͒ and cooling gas flow rates ͑N 2 at 0-2 l min −1 ͒ with a flow perpendicular to the upper facet of the chip.…”
mentioning
confidence: 94%
“…Such extraordinary properties make these materials promising for many energy-related applications, including electrochemical devices, 1 hydrogen storage, 2 catalytic supports, 1 compliant electrical contacts, 3 targets for inertial fusion energy, 4 and energy absorbing structures. 5 Conventional carbon aerogels (CAs), derived from carbonized resorcinol-formaldehyde polymeric gels, are prototypical monolithic nanoporous carbons. 6 Recently, there have been a number of reports on the synthesis of carbon-nanotube (CNT) based nanofoams with improved properties compared to those of conventional CAs (see, for example, Refs.…”
mentioning
confidence: 99%
“…Hence, heavy-ion irradiation could, for example, be used for the formation of multilayer nanoporous structures with variable stiffness and failure parameters, with the layer thickness controlled by ion energy. These multilayer structures could be attractive for minimizing contact and wear damage in energy absorbing structures 3 and compliant electrical contacts. 32 …”
Section: Summary Of Heavy-ion-induced Modification Of Carbon Aeromentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] For example, Worsley et al 5,11 have demonstrated composites of CNTs and conventional CAs (which we will refer to as "CNT-CAs") with a three dimensional network of CNT bundles decorated and cross-linked by graphitic carbon nanoparticles. As compared to conventional CAs, such CNT-CAs have enhanced mechanical stiffness and electrical conductivity 5,11 Properties of nanofoams can be tuned for specific applications by post-synthesis processing.…”
Section: Introductionmentioning
confidence: 99%